Urgensi inovasi pembelajaran pada mata pelajaran sejarah - Hilmiah, Anis Syatul (Peneleh Research Institute, 2024)
The aim of this research is to understand the importance of innovation in history learning. This research uses the library research method. The research results show that innovation in history learning is clearly important to carry out because it has many benefits.